2023
DOI: 10.1111/1365-2745.14098
|View full text |Cite|
|
Sign up to set email alerts
|

Evenness mediates the global relationship between forest productivity and richness

Abstract: 1. Biodiversity is an important component of natural ecosystems, with higher species richness often correlating with an increase in ecosystem productivity. Yet, this relationship varies substantially across environments, typically becoming less pronounced at high levels of species richness. However, species richness alone cannot reflect all important properties of a community, including community evenness, which may mediate the relationship between biodiversity and productivity. If the evenness of a community … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 87 publications
1
3
0
Order By: Relevance
“…Thus, our results showed that the growth of both Eucalyptus and mixed native trees was promoted with an increased intercropping ratio of native trees. Considering the increased evenness of trees with the increased intercropping ratio of native trees (indicated by SWI and PI), our results also confirmed the important effect of evenness on productivity of forests with high species richness (Hordijk et al, 2023).…”
Section: F I G U R Esupporting
confidence: 81%
“…Thus, our results showed that the growth of both Eucalyptus and mixed native trees was promoted with an increased intercropping ratio of native trees. Considering the increased evenness of trees with the increased intercropping ratio of native trees (indicated by SWI and PI), our results also confirmed the important effect of evenness on productivity of forests with high species richness (Hordijk et al, 2023).…”
Section: F I G U R Esupporting
confidence: 81%
“…PSPs data has been collated within plot networks at the regional, continental and now global scale 22 , 29 31 and combined with other forest inventory plots or unstructured data (like species occurrences) to address global ecological questions and biodiversity issues. Recent studies examined the relationship between forest biodiversity and productivity 32 , 33 , the number of tree species in the tropics 34 and on Earth 35 , invasion by non-native tree species 36 , or the forest carbon potential 37 thanks to new approaches in data analysis like machine learning or artificial intelligence allowing to deal with massive but heterogeneous data.…”
Section: Background and Summarymentioning
confidence: 99%
“…And because the effects of introductions cascade through interaction networks, it is often difficult to predict whether they will reinforce or undermine the integrity of a given ecosystem [11,18,19]. Thus, attempting to artificially increase complexity can have unintended consequences [13,20,21] and entail trade-offs with other desirable system features, like resilience, robustness, or productivity [16,[22][23][24].…”
Section: More Complexity Is Not Always Bettermentioning
confidence: 99%